2015
DOI: 10.1080/17470218.2015.1008526
|View full text |Cite
|
Sign up to set email alerts
|

Getting connected: Both associative and semantic links structure semantic memory for newly learned persons

Abstract: . (2015) 'Getting connected : both associative and semantic links structure semantic memory for newly learned persons.', Quarterly journal of experimental psychology., 68 (11). pp. 2131-2148.Further information on publisher's website:https://doi.org/10. 1080/17470218.2015.1008526 Publisher's copyright statement:This is an Accepted Manuscript of an article published by Taylor Francis Group in Quarterly journal of experimental psychology on 02/03/2015, available online at: http://www.tandfonline.com/10. 1080/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Later repetition effects between 375-537ms from stimulus onset differed in direction and topography to previously reported face repetition or semantic/categorical priming effects at similar latencies (e.g. Schweinberger et al, 2002;Wiese & Schweinberger, 2015). These repetition effects may index influences on local recurrent network activity, as found in macaque inferior temporal neurons (Kaliukhovich & Vogels, 2016) and in V1 (Patterson et al, 2013).…”
Section: Stimulus Repetition Effectsmentioning
confidence: 49%
“…Later repetition effects between 375-537ms from stimulus onset differed in direction and topography to previously reported face repetition or semantic/categorical priming effects at similar latencies (e.g. Schweinberger et al, 2002;Wiese & Schweinberger, 2015). These repetition effects may index influences on local recurrent network activity, as found in macaque inferior temporal neurons (Kaliukhovich & Vogels, 2016) and in V1 (Patterson et al, 2013).…”
Section: Stimulus Repetition Effectsmentioning
confidence: 49%
“…Our work thus expands the pool of domains by which to study the nature and organization of self-knowledge and semantic memory. Moreover, it seems fruitful for future work to examine similarities and differences between the processing of self-knowledge and knowledge of individual people more generally, as ERP studies of person-specific processing have also reported both N400 (e.g., Wiese and Schweinberger, 2015) and LPC (Bartholow et al, 2001) effects.…”
Section: Discussionmentioning
confidence: 99%
“…Waveform modulations reported as N400 effects have been observed for familiar faces and argued to reflect access to semantic representations (Wiese and Schweinberger, 2015, Schweinberger, 1996; Schweinberger and Burton, 2003). Bruce and Young (1986) distinguish between visually-derived and identity-specific semantics, referring to information that is derived from a face without the face necessarily having to be identified, and the knowledge that supports person identification, respectively.…”
Section: Discussionmentioning
confidence: 99%